Structural Elucidation of Borate Glasses by Spectroscopic and SEM Studies - Thirumaran, S.; Priyadharsini, A. (Asian Journal of Chemistry, 2018)
Glass samples of composition (B2O3-WO3-Bi2O3) BTB glass systems and (B2O3-SiO2-Bi2O3) BSB glass systems with ranging from 2 mol % are prepared by melt quenching technique. The structural analysis of glasses is analyzed by Fourier-transform infrared, UV-visible and scanning electron microscopy studies. The FTIR spectrum identifies the broad absorption bands indicated the wide distribution of borate structural units. The UV-visible study observes the increasing band gap energies of glass specimen suggesting their nature of rigidity. The surface morphological aspects of the prepared glass samples are examined by scanning electron microscopy study.